2019
DOI: 10.1111/ecin.12763
|View full text |Cite
|
Sign up to set email alerts
|

Life After Debt: Postgraduation Consequences of Federal Student Loans

Abstract: We estimate the causal effect of student loans on postgraduation labor market outcomes exploiting a kink in the formula determining eligibility for need‐based student loans. Using a representative sample of students graduating with a bachelor's degree in 1993, we find that student debt has nonnegative effects on earnings. This result holds with differing levels of statistical significance across a battery of different empirical designs: (1) ordinary least squares, (2) partially linear, and (3) regression kink.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…From this question, 112 students out of the 148 had selected that they planned on relying on their parents to aid them in repaying their borrowed money. This finding was similar to that of Gervais and Ziebarth (2019) because in their study they claimed that 63% of the graduates received financial assistance from their parents and that a majority depend on their family for financial assistance. This is significant because the findings corroborate each other in that both investigations found that parents played a somewhat large role in the student's post-graduate financial situation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…From this question, 112 students out of the 148 had selected that they planned on relying on their parents to aid them in repaying their borrowed money. This finding was similar to that of Gervais and Ziebarth (2019) because in their study they claimed that 63% of the graduates received financial assistance from their parents and that a majority depend on their family for financial assistance. This is significant because the findings corroborate each other in that both investigations found that parents played a somewhat large role in the student's post-graduate financial situation.…”
Section: Discussionsupporting
confidence: 79%
“…He also found that for the investment to pay off, borrowers feel a strong pressure to get a high paying job right out of the gate. Relating to the idea of getting a high paying job, Gervais and Ziebarth (2019) commented that many individuals should feel inclined to go out and attempt to work in riskier fields, such as the medical field, where there is a large investment involved but the return is much greater. Some of these jobs don't allow for students to repay their loans due to the salary and having to pay for items that are necessary to live.…”
Section: Student Debtmentioning
confidence: 99%
“…When policymakers increase access to student loans, they trade off potential benefits, including human capital accumulation, against potential costs, including increased default and distortions to economic decisions. 3 Beyond the direct effects of human capital accumulation and default, student loans affect homeownership (Goodman, Isen, and Yannelis, 2018;Mezza et al, 2018), earnings (Gervais and Ziebarth, 2016), and occupational choice (Rothstein and Rouse, 2011). In addition, schools capture a large amount of federal loans through tuition (Lucca et.…”
Section: Introductionmentioning
confidence: 99%
“…15 Increases in student loans have been linked to post-college job choice (Rothstein and Rouse, 2011), co-residence with parents (Dettling and Hsu, 2018), graduate education (Chakrabarti et al, 2020), entrepreneurship (Krishnan and Wang, 2019), homeownership (Goodman et al, 2018;Mezza et al, 2020) and family formation (Goodman et al, 2018). Gervais and Ziebarth (2019) provide suggestive evidence that borrowing leads to higher wages, but this finding is sensitive to the specification and time frame considered, and the underlying analysis sample is selected based on a potentially endogenous outcome (college graduation). 16 Goodman et al (2018) and Denning (2019) analyze the effects of a change in federal loan limits (and, potentially, Pell Grant awards) that occurs when a student becomes old enough to be considered financially independent (age 24) and, thus, focus on a relatively specialized population (i.e., traditional students that take longer than four years to complete college or nontraditional students).…”
mentioning
confidence: 99%